Developing Empathy for Older Users in Undergraduate Design Students - Woodcock, Andree; McDonagh, Deana; Osmond, Jane (Design and Technology Education: An International Journal, 2018)
Empathy has been recognised as a key skill by practicing designers. With rapid changes to inclusivity and accessibility in the transport sector, student designers need to appreciate and understand the way in which people of differing abilities are able to engage with and interact with transport. They need to not only develop an understanding of older and vulnerable users - how they experience products, vehicles, services and systems - but also have the confidence to try out new ways of finding information and gaining ‘authentic experiences’ to feed into their designs. Although empathic design is encouraged, there is often little opportunity for this to occur in a full educational curriculum. To meet this need, the authors are developing a framework for teaching empathic design using low fidelity, experiential prototypes – using material that is easily available and affordable to design students. This paper reports the first steps towards designing a brief intervention to increase the empathic horizon of transport design students. It concludes with recommendations on how to create high quality learning experiences for students that will enable enhanced empathic design outcomes as they embark upon design careers.